Falsification of Marriage Registration Data in Unauthorized Polygamy Practices: A Juridical Analysis Based on Article 391 of Law Number 1 of 2023 - Tety Andriani; Tina Amelia (Journal Customary Law, 2026)
Marriage registration in Indonesia is not merely an administrative requirement, but a legal mechanism intended to secure certainty and protect the rights of those within a marital relationship, particularly women and children. In practice, however, this framework is not always observed, as instances of unauthorized polygamy continue to occur, often accompanied by the falsification of marital status in order to bypass legal requirements. This article examines how such conduct is constructed and qualified within Indonesian law, with specific reference to Article 391 of Law No. 1 of 2023 on the Criminal Code. Using a normative juridical approach based on statutory and conceptual analysis, the study draws upon relevant legislation and legal doctrine to assess the issue. It finds that falsification of data in marriage registration cannot be viewed solely as an administrative or civil irregularity, but rather as conduct that may satisfy the elements of a criminal offence. While the Marriage Law places strict limitations on polygamy, these safeguards are frequently circumvented through false declarations or concealment of prior marital status. In this respect, Article 391 provides a more adaptive legal basis than earlier provisions, as it accommodates developments such as electronic documentation and introduces alternative sanctions in the form of fines. The implications of such practices are far-reaching, affecting not only the legal position of spouses and children but also the reliability of the population administration system. For this reason, addressing unauthorized polygamy requires more than civil remedies alone; it calls for a combination of administrative reform, improved data verification, greater legal awareness, and consistent application of criminal law to ensure that the underlying conduct is properly addressed.